Fructooligosaccharides integrity after atmospheric cold plasma and high-pressure processing of a functional orange juice. (December 2017) - Almeida, Francisca Diva Lima; Gomes, Wesley Faria; Cavalcante, Rosane Souza; Tiwari, Brijesh K.; Cullen, Patrick J.; Frias, Jesus Maria; Bourke, Paula; Fernandes, Fabiano A.N.; Rodrigues, Sueli
Abstract: In this study, the effect of atmospheric pressure cold plasma and high-pressure processing on the prebiotic orange juice was evaluated. Orange juice containing 7 g/100 g of commercial fructooligosaccharides (FOS) was directly and indirectly exposed to a plasma discharge at 70 kV with processing times of 15, 30, 45 and 60 s. For high-pressure processing, the juice containing the same concentration of FOS was treated at 450 MPa for 5 min at 11.5 °C in an industrial equipment (Hyperbaric, model: 300). After the treatments, the fructooligosaccharides were qualified and quantified by thin layer chromatography. The organic acids and color analysis were also evaluated. The maximal overall fructooligosaccharides degradation was found after high-pressure processing. The total color difference was < 3.0 for high-pressure and plasma processing. citric and ascorbic acid (Vitamin C) showed increased content after plasma and high-pressure treatment. Thus, atmospheric pressure cold plasma and high-pressure processing can be used as non-thermal alternatives to process prebiotic orange juice. Graphical abstract: Highlights: Prebiotic orange juice was non-thermal processed. Multifactorial analysis was applied to evaluate the effect of treatments. High pressure processing resulted in the highest oligosaccharides changes. No perceptive color difference was observed after the non-thermal treatments. Vitamin C was well preserved in all treatments.